Predisposing Factors for Nutritional Rickets in Children Presenting in Shaikh Zayed Hospital, Lahore - Asfand Tariq, Asim Noor Cheema, Abdul Matin Qaisar, Lubna Riaz, Neelam Faryad, Kashif Hussain, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Nutritional rickets resulting from different causes continue to be a major pediatric concern in many developing countries. It's the most frequent non-communicable disease among children globally. Even developed countries have not been exempted from this disease. Aim: To determine the predisposing factors for nutritional rickets in children, presenting in Shaikh Zayed Hospital Lahore Study design: Cross sectional study Place and duration of study: Department of Pediatric Medicine, Sh. Zayed Hospital, Lahore from 01-01-2019 to 31-07-2019. Methodology: One hundred and thirty children of nutritional rickets were enrolled. Children of both genders and age 9 months to 2 years were included. All children on anti-convulsant therapy and chronic liver diseases were excluded. Results: There were 83(63.85%) between 9-18 months, 47(36.15%) were between 19-24 months of age with mean age was 17.36±3.92 months. Seventy four (56.92%) males and 56(43.08%) were females. Predisposing factors reveal 89(68.46%) exclusive breast feeding, 68(52.31%) low nutritious status of mother, 93(71.54%) had cow’s milk, 87(66.92%) had lack of sunlight exposure and 63(48.46%) had malnutrition. Conclusion: Exclusive breast feeding, low nutritious status of mother, cow’s milk, lack of1sunlight exposure and malnutrition are the significant predisposing factors for nutritional rickets in children.